Fast sequential Monte Carlo methods for counting and optimization - Rubinstein, Reuven Y.; Ridder, Ad, 1955-; Vaisman, Radislav (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
This book presents the first comprehensive account of fast sequential Monte Carlo (SMC) methods for counting and optimization at an exceptionally accessible level. Written by authorities in the field, it places great emphasis on cross-entropy, minimum cross-entropy, splitting, and stochastic enumeration. The overall aim is to make SMC methods accessible to readers who want to apply and to accentuate the unifying and novel mathematical ideas behind SMC in their future studies or work.
A.3 Efficiency of EstimatorsBibliography; Abbreviations and Acronyms; List of Symbols; Index; Series
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Monte Carlo method; Mathematical optimization; MATHEMATICS -- Numerical Analysis; Mathematical optimization; Monte Carlo method; Sequentielle Monte-Carlo-Methode.; Optimierung; Electronic books